Mitochondrial respiratory complex II is altered in renal carcinoma - Miklovicova, Sona; Volpini, Luca; Sanovec, Ondrej; Monaco, Federica; Vanova, Katerina Hadrava; Novak, Jaromir; Boukalova, Stepana; Zobalova, Renata; Klezl, Petr; Tomasetti, Marco; Bobek, Vladimir; Fiala, Vojtech; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2025)
BACKGROUND: Renal cell carcinoma (RCC) is a disease typified by anomalies in cell metabolism. The function of mitochondria, including subunits of mitochondrial respiratory complex II (CII), in particular SDHB, are often affected. Here we investigated the state and function of CII in RCC patients. METHODS: We evaluated tumour tissue as well as the adjacent healthy kidney tissue of 78 patients with RCC of different histotypes, focusing on their mitochondrial function. As clear cell RCC (ccRCC) is by far the most frequent histotype of RCC, we focused on these patients, which were grouped based on the pathological WHO/ISUP grading system to low- and high-grade patients, indicative of prognosis. We also evaluated mitochondrial function in organoids derived from tumour tissue of 7 patients. RESULTS: ccRCC tumours were characterized by mutated von Hippel-Lindau gene and high expression of carbonic anhydrase IX. We found low levels of mitochondrial DNA, protein and function, together with CII function in ccRCC tumour tissue, but not in other RCC types and non-tumour tissues. Mitochondrial content increased in high-grade tumours, while the function of CII remained low. Tumour organoids from ccRCC patients recapitulated molecular characteristics of RCC tissue. CONCLUSIONS: Our findings suggest that the state of CII, epitomized by its assembly and SDHB levels, deteriorates with the progressive severity of ccRCC. These observations hold the potential for stratification of patients with worse prognosis and may guide the exploration of targeted therapeutic interventions.
Keywords: nádory ledvin; Mitochondria; Humans; respirační komplex II; lidé středního věku; Von Hippel-Lindau Tumor Suppressor Protein; mitochondriální DNA; Carbonic Anhydrase IX; Female; mutace; Aged; dospělí; DNA, Mitochondrial; senioři; lidé; mitochondrie; karboanhydrasa IX; Antigens, Neoplasm; sukcinátdehydrogenasa; antigeny nádorové; Adult; Electron Transport Complex II; ženské pohlaví; Male; Middle Aged; karcinom z renálních buněk; Carcinoma, Renal Cell; Mutation; Succinate Dehydrogenase; mužské pohlaví; nádorový supresorový protein VHL; Kidney Neoplasms